Outcome measurements in patients with a lumbar disc herniation – a scoping review - N. Gabrovsky; M. Petrov; Y. Kotceva; Y. Petrova (Brain and Spine)
Introduction: Outcome measurement is a cornerstone of modern medicine. A range of tools are commonly used for outcome assessment in lumbar disc herniation (LDH) treatment. Research question: What are the outcome measurement tools (OMTs) that have been used in the randomized controlled trials (RCTs) for LDH for the last 25 years? Material and methods: The search covered only RCT of adult patients with LDH for the period January 01, 2000–December 31, 2024. Two authors reviewed independently the RCTs’ relevance to the topic of our scoping review. The reviewed and selected RCTs were analyzed, and relevant data was extracted, standardized and classified. Results: We identified 168 RCTs and 29 outcome measurement tools covering 6 main domains: pain measurement – 6 tools, disability – 4 tools, quality of life – 2 tools, clinical parameters – 9 tools, psychological facet – 3 tools and self-perceived recovery – 5 tools. The number of tools used per RCT was most frequently 3 (26.2 %) or 4 (21.4 %). Discussion and conclusion: Measuring outcome in patients with LDH is a complex and multidimensional task. The RCTs involving surgical treatment usually applied tools from 4 domains: pain, disability, clinical parameters and QOL. The most frequently used tools for the different domains were respectively: VAS, ODI, a mixture of clinical parameters and SF-36/12. A new group of outcome measuring tools based on computer adapted tests, wearable devices and digital outcome measures are on the horizon trying to impose new standards but their application needs further investigation.